Emergent Epitaxial Configuration of Pr3IrO7 Domains via YSZ (111) Substrate - Gahee Noh; Lu Guo; Pratap Pal; Neil Campbell; Mark Steven Rzchowski; Chang‐Beom Eom; Si‐Young Choi (Small Structures)
The 5d rare Earth iridate is an intriguing material with exhibiting exotic electronic and magnetic phases due to spin‐orbit coupled states. Ternary iridium oxides Ln3IrO7 contain an unusual Ir5+ (5d4) system, which remain a subject of active research. Fabricating epitaxial Ln3IrO7 films is challenging due to substrate compatibility, but it offers a valuable platform to explore electronic and magnetic behaviors under reduced dimensionality and substrate interactions, revealing novel phenomena based on Ir5+ (5d4). In this regard, this demonstrates that Pr3IrO7 with its highly anisotropic orthorhombic structure can be epitaxially grown on a cubic (111)‐oriented yttrium‐stabilized ZrO2 (YSZ) substrate. Pr3IrO7 film exhibits six epitaxial domains, where the (220) and (202) planes aligning epitaxially to YSZ (111) with the threefold symmetry. This diverse domain configuration in Pr3IrO7 film leads to unique magnetic properties, exhibiting spin‐glass‐like behavior. Pr3IrO7 thin film offers a platform for exploring unconventional magnetic states, and their successful heteroepitaxy on YSZ substrates opens new avenues for discovering novel physical phenomena.